Depressive Symptoms and Work-Related Stress in Chilean Workers: Differential Conditions for Males and Females [Síntomas Depresivos y Distrés Laboral en Trabajadores Chilenos: Condiciones Diferenciales Para Hombres y Mujeres] - Montano-Espinoza, R (Fundacao Oswaldo Cruz, 2014)
This article assessed depressive symptoms associated with work-related psychosocial risk factors according to gender in Chile, using the demand-control model (Karasek) and effort-reward imbalance (Siegrist). A cross-sectional study was conducted in a random sample of 3,010 workers (35% female and 65% male) from the country. Data analysis determined prevalence and associations through various statistical techniques (?2, logistic regression). Exposure to psychosocial risk factors at work and prevalence of depressive symptoms were higher in women than men (15% vs. 5%). The adjusted analysis highlighted that female workers exposed to Isostrain (OR = 2.34; 95%CI: 1.42-3.85) and low rewards (OR = 2.13; 95%CI: 1.41-3.21) and male workers exposed to psychological demands (OR = 3.04; 95%CI: 1.94-4.76) and effort-reward imbalance (OR = 2.19; 95%CI: 1.39-3.46) had increased risk of depressive symptoms. Exposure to work-related psychosocial risk factors was associated with depressive symptoms in Chilean workers. Effective prevention in key aspects of work organization is thus needed.